Statistical Analysis of Time and Cost Efficiency of Construction Dispute Resolution Through Mediation Compared to Arbitration - Lutfi Mustakim; Sami’an; Sarwono Hardjomuljadi (Dinasti Research, 2025)
Non-litigation conflicts can be settled in a number of ways, including through arbitration and mediation.